The leading importance of architectural conservation areas for the establishment of a modern system of interactive recreation in historical cities - Hniloskurenko, Mariia V.; Skoryk, Larisa P.; Skoryk, Larisa P. (Linguistics and Culture Review, 2021)
The relevance of the study is conditioned by the fact that an architectural conservation area, as a rule, is part of the central territory of the city, which is subject to a special regime of protection of historical and cultural heritage and the status of the land of historical and cultural designation. Nowadays, in the structure of historical cities, there are a number of architectural conservation areas of both national and local significance, for which a special role is played by the unity and complexity of measures to preserve the historical planning structure and architectural substance. Preserving and increasing the historical and cultural values of the nature reserves environment is crucial for creating attractive interactive recreation areas. At the same time, it is of particular importance to determine the trends of interactive recreation in the conservation areas in the entire historical process to further develop the recreational opportunities of public urban spaces. The purpose of the study is to determine the attractions and recreational capacity, richness and diversity of elements of architectural and urban heritage in the territories of the conservation areas, which together constitute the potential for optimal development of the interactive recreation system.